The relationship between self-esteem and resilience of adolescents who living in orphanages - Budi Kurniawan; Neviyarni Neviyarni; Solfema Solfema (Universitas Negeri Padang, 2017)
Resilience is an important aspect for the psychososial development of adolescents who living in orphanages. Self-esteem is suspected to affect resilience of adolescents who living in orphanages. The purpose of this research is: (1) describes self-esteem and resilience adolescents who living in orphanages, and to know (2) the relationship between self-esteem and resilience of adolescents who living in orphanages. This research uses correlational method. Subjects in this research were 87 adolescents who living in 4 orphanages in Pariaman City with 13-18 of age. The data was collected using self-esteem scale and resilience scale. The data were analyzed using simple regression analyses by utilizing program SPSS 20.0 for Windows. Research results showed that: (1) generally self-esteem and resilience adolescents who living in orphanages are in the high category, and (2) there was significant positive relationship between self-esteem and resilience of adolescents who living in orphanages.